2014
DOI: 10.2535/ofaj.90.89
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the subscapularis tendon at the fetal glenohumeral joint

Abstract: Summary:We examined the topohistology of the subscapularis tendon at the glenohumeral joint in 10 mid-term (15-16 weeks of gestation) and 10 late-stage (27-32 weeks) human fetuses. At both stages, there were two patterns of terminal course of the subscapularis tendon: 1) the tendon was tightly attached to the medial part of the joint capsule and extended anterosuperiorly along the capsule to the lesser tubercle (7/10 mid-term fetuses; 5/10 late-stage fetuses); 2) the tendon passed superiorly through the joint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The brachialis is a major muscle that attaches to and stabilizes the anterior aspect of the humeroulnar joint in adults [ 3 , 4 ], whereas the flexor pollicis longus and others muscles cover the joint capsule in late-term fetuses [ 5 ]. In fetuses, the subscapularis muscle belly tends to extend into the glenohumeral joint cavity along the thick tendon [ 6 ]. Because the subscapularis tendon provides high resistance against mechanical stress in adults [ 7 ], the intra-articular muscle fibers should degenerate during shoulder movements in infants.…”
Section: Introductionmentioning
confidence: 99%
“…The brachialis is a major muscle that attaches to and stabilizes the anterior aspect of the humeroulnar joint in adults [ 3 , 4 ], whereas the flexor pollicis longus and others muscles cover the joint capsule in late-term fetuses [ 5 ]. In fetuses, the subscapularis muscle belly tends to extend into the glenohumeral joint cavity along the thick tendon [ 6 ]. Because the subscapularis tendon provides high resistance against mechanical stress in adults [ 7 ], the intra-articular muscle fibers should degenerate during shoulder movements in infants.…”
Section: Introductionmentioning
confidence: 99%
“…However, in adults, IP muscle fibres are unlikely to attach to the capsule because the IP tendon reinforces the weak anterior aspect of the joint as a dynamic stabiliser, acting as a supporting structure strengthened by muscle contractions, comparable to the relationship between the rotator cuff and the glenohumeral joint [13]. The subscapularis muscle tendon, the strongest rotator cuff tendon, showed a similar morphology [8], with this tendon in late stage foetuses composed of abundant fragments of muscle fibres [2]. Moreover, flexor muscle fibres attached to the capsule in foetal elbow joints were reported to degenerate after birth [5].…”
Section: Discussionmentioning
confidence: 99%
“…In adults, musculofibrous tissues from the supinator muscle belly often join the oblique cord [14]. Likewise, thickening of the foetal subscapularis tendon involves degeneration of parts of the muscle fibres [1]. These findings suggested that the oblique cord formed after birth under the influence of individual mechanical stresses during pronation-supination movements.…”
Section: Discussionmentioning
confidence: 99%